Challenges in the Healthcare-Seeking Behavior of International Students Living in Japan as Perceived by Japanese Language School Faculty and Staff - Kimura, Kiyoko; Morooka, Yuki (Journal of Japan Academy of Nursing Science, 2025)
Objective: This study aims to identify issues in the health-seeking behaviour of international students in Japan as perceived by teaching staff at Japanese language schools.Methods: We conducted semi-structured interviews with 10 teachers and staff from Japanese language schools. The data obtained were analysed using qualitative descriptive methods.Results: “Disadvantage in receiving medical examinations due to being an international student in Japan”, “Due to the limitations of Japanese language skills, conversations during medical examinations do not convey the true meaning”, “They have to rely on teachers to make decisions, including whether they need to see a doctor.” It was shown to be the case. In addition, “Due to differences in social systems and customs from their home country, they are not familiar with typical healthcare-seeking behaviors in Japan.” This they faced. “Health-seeking behaviours are burdensome due to residency in situations where economic resources are not available.” This has been shown to be the case.Conclusion: It has been suggested that, in order for international students living in Japan to make use of medical institutions, it is necessary not only to improve the systems on the part of the medical institutions but also to provide information to the students and Japanese language schools, and to establish support systems by medical professionals.